Management and prognosis of malignant peripheral nerve sheath tumors: The experience of the French Sarcoma Group (GSF-GETO). (March 2016) - Valentin, T.; Le Cesne, A.; Ray-Coquard, I.; Italiano, A.; Decanter, G.; Bompas, E.; Isambert, N.; Thariat, J.; Linassier, C.; Bertucci, F.; Bay, J.O.; Bellesoeur, A.; et al.
Abstract: Background: Malignant peripheral nerve sheath tumors (MPNST) are a rare subtype of soft tissue sarcoma. They can arise in irradiated fields, in patients with type 1 neurofibromatosis (NF1), or sporadically. MPNST exhibit an aggressive behaviour, and their optimal management remains controversial. An unsolved issue is whether NF1-related and sporadic forms of MPNST have a different prognosis, and should be managed differently. Material and methods: Adult and paediatric patients with histologically confirmed MPNST treated between 1990 and 2013 in French cancer centres of the GSF/GETO network, were included in this retrospective study. Results: A total of 353 patients (37% with NF1 and 59% with sporadic tumours) were analysed. Median age at diagnosis was 42 years (range 1–94). The majority of tumours developed in the limbs, were deep-seated and of high grade. Two hundreds and ninety four patients underwent a curative intent surgery. Among them, 60 patients (21%) had neoadjuvant treatment (mainly chemotherapy), and 173 (59%) had adjuvant treatment (mainly radiotherapy). For operated patients, median progression free and overall survival (OS) were 26.3 months and 95.8 months, respectively. In multivariate analysis, poor-prognosis factors for OS were high grade, deep location, locally advanced stage at diagnosis, and macroscopically incomplete resection (R2). NF1 status was not negatively prognostic, except in the recurrence or metastatic setting, where NF1-related MPNST patients treated with palliative chemotherapy showed worse survival than patients with sporadic forms. Conclusion: To our knowledge, our series is the largest study of patients with MPNST reported to date. For operated patients, we showed a worse prognosis for NF1-related MPNST, due to different clinical features at diagnosis, more than NF1 status itself. The French sarcoma group is now conducting correlative analyses on these patients, using the latest molecular tools. Highlights: The largest retrospective study concerning patients with MPNST. Type 1 neurofibromatosis (NF1) status itself is not a prognostic factor in patients with operable disease. NF1 patients have worse prognosis due to different tumoural features when diagnosed.